Photocatalytic degradation of methylene blue in aqueous media using magnesium-substituted copper ferrite as a magnetic catalyst - Mazurenko, Julia; Kaykan, Larysa; Moklyak, Volodymyr; Petryshyn, Mykhailo; Mazurenko, Oleksandr; Leleko, Sofiia (Physics and Chemistry of Solid State, 2024)
In this study, copper nanosized ferrites substituted with magnesium ions were synthesized using the sol-gel self-combustion method, with polyethylene glycol (MW 2000) serving as both fuel and chelating agent. Structural properties were investigated using X-ray diffraction. It was confirmed that all samples crystallized as cubic spinels with space group Fd3m. Optical studies showed band gaps increasing from 1.51 eV for CuFe2O4 to 1.62 eV for MgFe2O4, suggesting modifications in electronic structure due to magnesium substitution. Photocatalytic studies revealed that CuFe2O4 exhibited the most efficient degradation of Methylene Blue dye, with near-complete degradation at 160 minutes. Magnesium-substituted samples (x = 0.4 and x = 0.6) also showed significant degradation, though at a slower rate compared to pure CuFe2O4. Photocatalytic performance, particularly in degrading Methylene Blue, was evaluated using various kinetic models such as First- and Second-Order Kinetics, the Langmuir-Hinshelwood model, and the two-parameter Weibull distribution.